Nonlinear saturable absorption in antimonene quantum dots for passively Q‐switching Pr:YLF laser. Issue 9 (5th March 2021) - Wu, Hao; Xu, Jinlong; Zhang, Chi; Cui, Yinghao; Hu, Yonghong; Xie, Zhenda; Yan, Zhong
Abstract: Antimonene, a new member of monoelemental two‐dimensional crystals composed of antimony atoms, was predicted to possess high stability, as well as outstanding electrical and optical properties. Here, we report on the experimental results of productive, high‐quality synthesis of antimonene quantum dots (AQDs) via liquid‐phase exfoliation. The obtained AQDs exhibited excellent nonlinear saturable absorption. The modulation depth and the saturable intensity were found to be around 3.9% and 10.02 GW/cm 2, respectively. By using the AQDs saturable absorber in the 639 nm Pr:YLF laser, stable Q‐switching pulsed laser was realized. The maximum output power was 83 mW and the corresponding pulse width was 255 ns with a pulse repetition rate of 227 kHz. These results suggest that AQDs are a promising candidate for nonlinear optical applications. Abstract : Antimonene quantum dots (AQDs) were produced via liquid phase exfoliation. The obtained AQDs exhibited excellent nonlinear saturable absorption and stable Q‐switching was realized using the AQDs saturable absorber in the 639 nm Pr:YLF laser. The maximum output power was 83 mW and the corresponding pulse width was 255 ns with a repetition rate of 227 kHz.